2014
DOI: 10.1111/odi.12212
|View full text |Cite
|
Sign up to set email alerts
|

Calcification during bone healing in a standardised rat calvarial defect assessed by micro‐CTandSEMEDX

Abstract: Healing bone is immaturely calcified initially and proceeds calcification gradually, that is, as the bone volume increases, mineral increases in density and matures in quality, while organic components decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…Ca and P have accumulated in the bone matrix (* in d-i) at E16 and the area expands through week 1, matching the region of developing bone (* in a-c), whereas C becomes localized around bone (* in j-l). The area with higher concentrations of Ca and P shows a lower concentration of C. ratios decrease during bone development and healing in calvaria (5,12). Fourier transform infrared spectroscopy (FTIR) analysis indicated that the proportion of protein to mineral decreases during calvarial bone development (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca and P have accumulated in the bone matrix (* in d-i) at E16 and the area expands through week 1, matching the region of developing bone (* in a-c), whereas C becomes localized around bone (* in j-l). The area with higher concentrations of Ca and P shows a lower concentration of C. ratios decrease during bone development and healing in calvaria (5,12). Fourier transform infrared spectroscopy (FTIR) analysis indicated that the proportion of protein to mineral decreases during calvarial bone development (5).…”
Section: Discussionmentioning
confidence: 99%
“…The samples were reconstructed by using a software program (Tri3DBon64; Ratoc, Tokyo, Japan). The threshold for standardising micro-CT images for separating bone from soft tissue was determined, as previously reported (12).…”
Section: Micro-ctmentioning
confidence: 99%
“…Our data of R Ca/P (around 1.55) in AIS was in agreement with previous report of lower R Ca/P value in younger bone tissue and indicated adequate homeostasis of calcium and phosphorous deposition in AIS. The ratio of calcium to phosphorus (R Ca/P ) was widely accepted as an indicator for assessing the status of bone mineralization2526. Carbon (C) was determined as the reference to assess the calcium content in the bone tissue because of its abundant and relatively stable content and being the major component of bone tissue262728.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of calcium to phosphorus (R Ca/P ) was widely accepted as an indicator for assessing the status of bone mineralization2526. Carbon (C) was determined as the reference to assess the calcium content in the bone tissue because of its abundant and relatively stable content and being the major component of bone tissue262728. EDX scanning showed significantly lower R Ca/C in AIS, but there was absence of significant difference in R Ca/P between AIS and Con, suggesting decreased mineralization which was in agreement with more osteoid as indicated by histomorphometric analyses (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…However, aging‐related changes in the structure and function of osteocyte LCN might alter the ability of osteocytes to sense mechanical loading, orchestrate bone remodelling and detect microdamage by fluid flow resulting in delayed insufficient bone repair and fragile bone. Emerging evidence showed that osteocytes could release secretory factors at the fracture site and facilitate bone regeneration by robust cellular recruitment during fracture healing . Osteocytes expressed proteins known to play profound roles during the healing process.…”
Section: Introductionmentioning
confidence: 99%